2020
DOI: 10.1038/s41398-020-0738-5
|View full text |Cite
|
Sign up to set email alerts
|

A polygenic predictor of treatment-resistant depression using whole exome sequencing and genome-wide genotyping

Abstract: Treatment-resistant depression (TRD) occurs in~30% of patients with major depressive disorder (MDD) but the genetics of TRD was previously poorly investigated. Whole exome sequencing and genome-wide genotyping were available in 1209 MDD patients after quality control. Antidepressant response was compared to non-response to one treatment and non-response to two or more treatments (TRD). Differences in the risk of carrying damaging variants were tested. A score expressing the burden of variants in genes and path… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 48 publications
2
41
0
Order By: Relevance
“…Pathway analysis led to the identification of several biological mechanisms that mediate depression and antidepressant action. These can be grouped in some main clusters: axonal development, neuron differentiation and morphogenesis, neural-plasticity, excitatory neurotransmission, cytokines, immune response and regulation of gene expression ( Zeng et al , 2017 ; Wray et al , 2018 ; Howard et al , 2018 ; Fabbri et al , 2019a ).…”
Section: Pathway Analysis: Insights Into the Biological Mechanisms Ofmentioning
confidence: 99%
See 3 more Smart Citations
“…Pathway analysis led to the identification of several biological mechanisms that mediate depression and antidepressant action. These can be grouped in some main clusters: axonal development, neuron differentiation and morphogenesis, neural-plasticity, excitatory neurotransmission, cytokines, immune response and regulation of gene expression ( Zeng et al , 2017 ; Wray et al , 2018 ; Howard et al , 2018 ; Fabbri et al , 2019a ).…”
Section: Pathway Analysis: Insights Into the Biological Mechanisms Ofmentioning
confidence: 99%
“…Despite a probable neurodevelopmental component in a subgroup of cases, genetic studies provided quite convincing evidence that MDD pathogenesis and antidepressant action mostly involve modifications of neural-plasticity and neurotransmission, which are controlled by changes in gene expression patterns and influenced by the activity of the immune system ( Calabrese et al , 2014 ). In terms of specific pathways, association signals came from those modulating long-term potentiation, a persistent increase in synaptic strength following high-frequency synaptic stimulation, and second messengers mediating the cellular events activated by neurotrophins such as brain-derived neurotrophic factor ( BDNF ) ( Hunter et al , 2013 ; Fabbri et al , 2019a ). Excitatory neurotransmission is a key regulator of neural plasticity and neural survival, and in the central nervous system, the most common excitatory neurotransmitter is glutamate.…”
Section: Pathway Analysis: Insights Into the Biological Mechanisms Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Of course this poses another challenge, as to assign a clinical relevance to rare variants identified that have not previously been characterized. Recent evidence suggests that bioinformatic tools may successfully be applied to NGS (Fabbri et al, 2020a). Specific programs that can be used for this are Aldy, Astrolable, and Stargazer.…”
Section: Genotyping Challengesmentioning
confidence: 99%